1995
DOI: 10.1530/eje.0.1320086
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in goiter size by 131I therapy in patients with non-toxic multinodular goiter

Abstract: A retrospective follow-up study of 131I treatment was performed in 10 females (median age 48 years, range 40-74 years) with non-toxic multinodular goiter. The median dose of 131I given was 20 mCi (range 14-65 mCi). Thyroid volume was measured by ultrasonography. The median follow-up period was 26 months (range 12-68 months). Nine patients had a reduction of goiter size: thyroid volume decreased from 88 +/- 14.9 ml (mean +/- SEM) to 49 +/- 10.9 ml 1 year after 131I treatment. The relative decrease of goiter siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 6 publications
5
26
0
2
Order By: Relevance
“…In toxic multinodular goitres, in which case the primary goal is to cure hyperthyroidism, Nygaard et al (70) found a goitre reduction of 43% within 2 years. Similar results have been obtained in studies of the non-toxic multinodular goitre (71)(72)(73), with reductions ranging from 40 to 60%. The superiority of 131 I over L-T 4 has recently been shown in a randomised trial by Wesche et al (61).…”
Section: Efficacy Of 131supporting
confidence: 84%
“…In toxic multinodular goitres, in which case the primary goal is to cure hyperthyroidism, Nygaard et al (70) found a goitre reduction of 43% within 2 years. Similar results have been obtained in studies of the non-toxic multinodular goitre (71)(72)(73), with reductions ranging from 40 to 60%. The superiority of 131 I over L-T 4 has recently been shown in a randomised trial by Wesche et al (61).…”
Section: Efficacy Of 131supporting
confidence: 84%
“…We observed that patients with hypothyroidism after the treatment initially had higher TSH and lower fT4 levels. These results confirm the conclusions drawn by Wesche et al that subclinical hyperthyroidism is a protective factor against hypothyroidism after 131-I treatment [26].…”
Section: Discussionsupporting
confidence: 93%
“…The use of radioactive iodine ( 131 I) for MNG treatment has been described in several studies, showing a goiter size reduction ranging from 34 to 49% in the first year (7)(8)(9)(10)(11)(12)(13)(14). Most of this reduction occurs during the first three months after 131 I therapy (12).…”
Section: Introductionmentioning
confidence: 99%